(untitled) (GESTIÓN Y TENDENCIAS, 2025)
This article analyzes Law 21.719 of 2024 on Personal Data Protection in Chile, which will take effect in December 2026. The text highlights the main novelties and requirements compared to the old legislation, including an expanded redefinition of sensitive data to explicitly encompass biometric and genetic information. Furthermore, the new regulations require unequivocal, free, and informed consent , establish the right to data portability for data subjects , and legally oblige organizations to notify security incidents or breaches. Finally, it addresses the recommended role of the Data Protection Officer (DPO) and the significant organizational challenges to identify the location and achieve full traceability of the information’s life cycle.